Ekonomi Politik Media Lokal (Framing Pemberitaan Pelanggaran HAM Di Kalimantan Timur) - Sy. Nurul Syobah; Sabiruddin Sabiruddin (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
The backdrop of this research is set upon the fact that the media exist in the setting of a growing democracy. Media play strategic roles in responding to events. At the local level, local events result from the repeated process of production and reproductions by the press. One of such local events in East Kalimantan was the findings of the National Committee for Human Rights (KOMNAS HAM) on the human rights abuse related to extractive industries, as mentioned in the 2016 report of the organization and had been stated again in 2019. Thus, local media responded to such findings by producing news about it. The findings of this research are that local media, Times Indonesia (national media network), opted not to mention the abuses due to arguments on internal policy and limited resources available to conduct the journalistic activity. Other media, Samarinda Pos and Kaltim Kece, responded differently to the report. The differences regarding the responses of those media outlets are based on applying Robert N. Entman's framing analysis on problem definition, diagnosis of causes, moral judgment, and treatment recommendation. Moreover, this research also showcases the practice of commodification by the media when they talk about human rights abuses.